Retrospective Comparative Analysis of KRAS G12C vs. Other KRAS Mutations in mCRC Patients Treated With First-Line Chemotherapy Doublet + Bevacizumab - Giampieri, Riccardo; Lupi, Alessio; Ziranu, Pina; Bittoni, Alessandro; Pretta, Andrea; Pecci, Federica; Persano, Mara; Giglio, Enrica; Copparoni, Cecilia; Crocetti, Sonia; Mandolesi, Alessandra; Faa, Gavino; et al. (Frontiers in Oncology, 2021)
KRAS mutations in metastatic colorectal cancer(mCRC)define a subset of tumors who have primary resistance to anti-EGFR based therapy.Data concerning whether different KRAS mutations may also have a prognostic value are lacking.Furthermore,novel KRAS G12C inhibitors are currently in development.Aim of our analysis was to compare response rates in patients treated with first line chemotherapy doublet+Bevacizumab among different KRAS variants.Secondary end-points were progression free survival(PFS) and overall survival(OS). Methods: Patients with KRAS mutated mCRC treated with either FOLFIRI/FOLFOX/XELOX+Bevacizumab were eligible for enrollment.Propensity score matching(nearest method, 2:1 ratio)was used to define the two different groups of patients for comparison(KRAS G12C mutated vs other KRAS variants).Eastern-Cooperative-Oncology-Group-Performance-Status(ECOG PS),sex,metastatic site of involvement,synchronous vs metachronous metastatic disease,tumor sidedness,mucinous histology,primary tumor surgery,more than 2 lines of treatment for metastatic disease and radical surgery of metastases were used as matching factors.Response rate(RR)was calculated by RECIST 1.1 criteria.Both PFS and OS were calculated by Kaplan-Meier method.Level of statistical significance p was set at 0.05 for all tests. Results: One-hundred twenty patients were assessed.Fifteen out of 120(12%) were KRAS G12C mutated.In the whole cohort,59/120(49%)had partial response(PR),42/120(35%)had stable disease(SD), 19/120(16%) had progressive disease(PD).In KRAS G12C patients,4/15(27%)had PR,6/15(40%)had SD and the remaining 5/15(33%)had PD as best response.In patients with other KRAS mutations,55/105(52%)had PR, 37/105(35%)had SD and the remaining 13/105(12%)had PD as best response.The difference in RR between the two groups of patients was statistically significant(p=0.017).No difference in PFS(p=0.76)and OS(p=0.56)was observed. After matching,the difference in response rates between KRAS G12C mutated patients vs patients with other KRAS mutations remained statistically significant(p=0.016).KRAS G12C mutations were not associated with differences in sites of metastatic involvement,sex and ECOG-PS.Synchronous vs metachronous metastatic disease(p=0.039),age >75years(p=0.043) and mucinous histology(p=0.008)were more frequent in G12C mutated tumors. Conclusions: KRAS G12C mutations are associated with worse response rates compared to other KRAS variants when treated with standard chemotherapy-doublet+Bevacizumab. On the other hand, both PFS and OS were not significantly different. We believe that new treatment options focused on KRAS G12C inhibition should be tested mainly in first-line setting and in addition to standard chemotherapy-doublet+Bevacizumab for mCRC patients, as they might “fill the gap” in response rates that was seen in our study.